ANALYSIS OF THE IMPACT OF THE COVID19 PANDEMIC ON ONLINE FOOD SHOPPING - Margit CSIPKÉS; Dorina FODOR (Annals of the University of Oradea: Economic Science)
In our research, we analyzed the shopping habits that have developed due to the Covid-19 pandemic. The reason for this is that, as a result of the pandemic, consumers were forced to adapt to the new conditions, which caused a significant increase in online grocery shopping. In our research, we tried to examine the impact of Covid on the online food market. Consumer behavior is a complex pattern of behavior that is made up of many elements, from individual needs to environmental factors and available information. Within this, the purchase decision process plays a prominent role, which we analyzed in our research using a five-step model. The model spans from recognition to post-purchase evaluation and is key to understanding consumer satisfaction. In the early stages of the epidemic, panic buying occurred, which is why we considered it important to examine the topic. We examine the evolution of the number of online food orders, the popularity of online food shopping, and the issue of sustainability and environmental awareness in the field of online shopping. In order to review the topic, we conducted a questionnaire survey, as we found that the Covid-19 epidemic brought about fundamental changes in consumer behavior and online food shopping. In our research, we performed a detailed analysis based on the answers of the respondents. The obtained results can highlight the importance of sustainability and trust in digital transactions, as well as the evolution of modern consumer behavior and shopping preferences.